2017
DOI: 10.3390/beverages3010016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Contaminants Associated with Palm Wine from Nigeria Are Potential Food Safety Hazards

Abstract: Recent analysis of palm wine, a traditional drink fermented mainly by yeasts, revealed the presence of several chemicals that were not products of yeast fermentation. The chemicals included styrene, benzene, trimethyldioxolane, dichloromethane, methylene fluoride, dichloroethanol, benzylisoquinoline and tetraacetyl-D-xylonic nitrile. A review of the concentrations of these compounds in palm wine found that the benzene concentrations in all samples reviewed ranged from 56-343 ppm and were within permissible lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A starting point may be for the government to show more regulatory oversight. There is a consensus that regulatory oversight and better relationships with food producers could improve the current food safety deficiencies in Nigeria [86]. The government should constantly review food safety elements such as leadership, communication, risk perception, self-commitment, and management support.…”
Section: Limitations In Promoting Food Safety Culture In Nigeriamentioning
confidence: 99%
“…A starting point may be for the government to show more regulatory oversight. There is a consensus that regulatory oversight and better relationships with food producers could improve the current food safety deficiencies in Nigeria [86]. The government should constantly review food safety elements such as leadership, communication, risk perception, self-commitment, and management support.…”
Section: Limitations In Promoting Food Safety Culture In Nigeriamentioning
confidence: 99%
“…Beverages 2020, 6, x; doi: FOR PEER REVIEW www.mdpi.com/journal/beverages Palm wine (Figure 3A) is a milky white alcoholic drink obtained from different species of palm trees around the world. Unregulated sales are rampant in Nigeria and despite some food safety hazards associated with the drink [24], it is believed to have oenological potentials [106] and maybe be suitable as a probiotic [107] or functional beverage [108]. The drink is obtained by making incisions on the tree to collect the sap, which predisposes the drink to environmental contamination.…”
Section: Pitomentioning
confidence: 99%
“…The origin of bacterial or fungal contaminations during the processing of many local food and beverages in Nigeria is unclear and the prevalence of microorganisms needs further characterization. Besides, microbial fermentation products of local drinks in Nigeria are poorly studied while it has been shown that the microorganisms responsible for the fermentation of traditional drinks may produce other compounds or derivatives, which are harmful to health [24]. Therefore, this work aims to review different microbial genera already associated with some unregulated beverages in Nigeria and the impact it may have on public health.…”
Section: Introductionmentioning
confidence: 99%
“…Some commonly consumed fermented foods include miso, soy paste, natto, and vinegar from East and Southeast Asia and yogurt, cheese, and kefir from Europe and America [6][7][8]. Other traditionally fermented foods include pickled fruit and vegetables and fermented beverages (e.g., beer, wine, and tea) from cereals and plants [9,10].…”
Section: Introductionmentioning
confidence: 99%